2016
DOI: 10.15448/1980-6108.2015.4.21443
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos dos alongamentos estático, balístico e facilitação neuromuscular proprioceptiva sobre variáveis de salto vertical

Abstract: Este artigo está licenciado sob forma de uma licença Creative Commons Atribuição 4.0 Internacional, que permite uso irrestrito, distribuição e reprodução em qualquer meio, desde que a publicação original seja corretamente citada. http://creativecommons.org/licenses/by/4.0/deed.pt_BR Efeitos dos alongamentos estático, balístico e facilitação neuromuscular proprioceptiva sobre variáveis de salto vertical Effects of static, ballistic, and proprioceptive neuromuscular facilitation stretching on vertical jump varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
2
0
5
Order By: Relevance
“…Place et al (2013) didn't recommend PNF protocol used unassisted for sportive activities in which flexibility is prioritized even though they showed that it doesn't affect jumping performance and isometric peak torque negatively. Ferreira et al (2015) showed it will not have a negative effect on vertical jump performance at least at a 4 weeks period. But this study is quite low volume (4 weeks, 1 time in a week, 30 s).…”
Section: Null Effects Of Pnf Stretching On Athletic Performancementioning
confidence: 98%
See 1 more Smart Citation
“…Place et al (2013) didn't recommend PNF protocol used unassisted for sportive activities in which flexibility is prioritized even though they showed that it doesn't affect jumping performance and isometric peak torque negatively. Ferreira et al (2015) showed it will not have a negative effect on vertical jump performance at least at a 4 weeks period. But this study is quite low volume (4 weeks, 1 time in a week, 30 s).…”
Section: Null Effects Of Pnf Stretching On Athletic Performancementioning
confidence: 98%
“…Some research results indicated that PNF stretching can be done before sport practice without a decrease on muscular strength when it's done at enough duration and consistence (Almeida et al 2009, Oliveira et al 2016 and it doesn't create a negative effect on vertical jump performance (Ferreira et al 2015). Thusly, in review studies long duration stretching exercises were put forward to create a positive effect on performance (Ferrari & Teixeira-Arroyo 2013, Stone et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison between proprioceptive neuromuscular facilitation and static stretching in flexibility in gymnastics A técnica chamada alongamento estático é a mais simples e utilizada, apresenta o menor risco de lesão; é uma das mais usadas por ser prática em relação ao tempo e a espaços limitados, podendo ser realizada em qualquer lugar (ROSARIO; MARQUES; MALUF, 2004). Pode ser realizado com ajuda de outra pessoa ou não, quando atingido a amplitude desejada é mantido de forma estática na mesma posição com uma tensão isométrica, que apresenta melhores resultados quando realizada por cerca de 30 segundos (BERTOLINI et al, 2008;FERREIRA et al, 2015).…”
Section: Comparação Entre Facilitação Neuromuscular Proprioceptiva E unclassified
“…A eficiência dos diferentes métodos de alongamento é um fator que assume questionamentos quanto aos seus efeitos imediatos sobre a força, implicando em prejuízos sobre a mesma (Almeida et al, 2011;Endlich et al, 2009;Paulo et al, 2012;Ribeiro et al, 2016) ou não (Ayala, Croix, Baranda & Santoja, 2015;César, Silva & Rezende, 2018;Ferreira, Bertor, Carvalho & Bertonini, 2015) e, especialmente, sobre os efeitos crônicos, na qual estudos não apresentaram efeitos deletérios dos métodos supracitados sobre o desempenho neuromuscular (Barbosa, Dantas, Silva, Souza & Vieira, 2018;Konrad, Gad & Tilp, 2015;Minshull, Eston, Bailey, Rees & Gleeson, 2014).…”
Section: Introductionunclassified